Does location of rapid influenza diagnostic testing influence treatment time and ancillary testing in a paediatric emergency department?. (17th August 2020) - Jacob, Ron; White, Brent; McCaskill, Mary E
Abstract: Objective: Influenza causes a significant burden of disease. Our aim was to assess whether location of rapid influenza diagnostic testing (RIDT) for patients with influenza‐like illness (ILI) has an impact on ED treatment time or ancillary testing. Methods: This was a retrospective observational study in a tertiary paediatric ED during 2017 influenza season. All patients with ILI were included. Some had RIDT performed (ED bedside or at the laboratory). Primary outcome measure was the correlation of RIDT location to treatment time compared to patients with ILI with no RIDT. Secondary outcome measures were the correlation of RIDT location to ancillary testing and treatment with antibiotics. Results: A total of 1451 patients with ILI were included. Eighty patients for whom RIDT was performed at the laboratory had a shorter treatment time in the ED when compared to the 215 patients for whom RIDT was performed bedside (2.8 and 3.4 h, respectively; P < 0.0001). However, treatment time was not statistically different when sub‐analysed for admitted and discharged patients separately. Overall, patients with ILI and no RIDT had the shortest treatment time in the ED (1.7 h). There was no difference in ancillary testing and treatment with antibiotics between ILI patients for whom RIDT was performed bedside or at the laboratory regardless of admission. Conclusion: Location of RIDT may not have a significant impact on treatment time, ancillary testing and treatment with antibiotics. When RIDT was not performed, patients had the shortest treatment time.